Perencanaan dan Pengembangan Mobile Learning Berbasis Website pada Mata Kuliah Organisasi dan Manajemen - Rahman Hasim; Azizah Mujahidah Annisa; Adrianto Adrianto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Mobile learning provides benefits including providing the latest facilities and library resources, as well as making it easy to access (when, where, and by anyone) without space and time limits, supporting student-centered learning processes, providing a variety of learning resources, and as a learning medium. independent. The purpose of this research is how the planning and development stage of website-based mobile learning in Organization and Management courses as an innovative learning medium in the State Administration (S1) study program, FHISIP Universitas Terbuka. This researcher uses the Research and Development (R&D) type of research. The making of mobile learning media is adapted from the Borg & Gall (2003) model which consists of ten stages and then summarized into three parts, namely planning, development, and evaluation. This research focuses on the planning and development section. Data collection techniques in this study used questionnaires and interviews. The results of this study are the design of the website display and the making of learning videos and then testing the effectiveness of the learning media that is being developed.